Peningkatan Pengetahuan tentang Kesehatan Reproduksi Remaja Putri dengan Metode Teleconference di Masa Pandemi - Umi Aniroh; Tina Mawardika; Purbowati Purbowati (UNIVERSITAS NGUDI WALUYO, 2022)
In order to support the government's efforts to provide quality health services to adolescents, especially young women, it is necessary to involve health educators to conduct education about Increasing Knowledge about Adolescent Reproductive Health with the Teleconference Method. Problems during menstruation are not only related to cleanliness but also about the emergence of health problems during menstruation. Education on Increasing Knowledge about Adolescent Reproductive Health with the Teleconference Method needs to be given to young women who are still in school. Schools that can be used as partners in this effort include schools whose students are mostly female so that the education that will be provided is right on target. Based on the survey, it is known that students at the Nahdlatul Ulama Vocational School have never received education about Increasing Knowledge about Adolescent Reproductive Health with the Teleconference Method. The implementation of this community service activity is carried out by providing education to Nahdlatul Ulama Vocational High School students online using a zoom meeting platform. The percentage of evaluation results before being given education was in the category of not understanding as much as 13.88%, quite understanding 21.82%, good understanding 56.71% and very good 7.59%. The understanding of female students has increased after being given education, which is included in the very good category by 28.82%, good 53.94%, sufficient 7.82% and less as much as 9.42%. Thus it is known that after being given education there is an increase in students' understanding of Adolescent Reproductive Health. Based on statistical analysis (Wilcoxon test) obtained a significance value of 0.002 < 0.05, which means that there is a significant difference in the level of knowledge between before and after education. Increasing Knowledge about Reproductive Health for Adolescent Girls with the Teleconference Method.ABSTRAKDalam rangka mendukung upaya pemerintah untuk memberikan pelayanan kesehatan yang berkualitas kepada remaja, khususnya pada remaja putri maka diperlukan keterlibatan tenaga pendidik bidang kesehatan untuk melakukan edukasi tentang Peningkatan Pengetahuan tentang Kesehatan Reproduksi Remaja dengan Metode Teleconfrence. Permasalahan pada saat terjadi menstruasi tidak hanya terkait tentang kebersihannya tetapi juga tentang munculnya gangguan kesehatan saat menstruasi. Edukasi tentang Peningkatan Pengetahuan tentang Kesehatan Reproduksi Remaja dengan Metode Teleconfrence perlu diberikan pada remaja putri yang masih berada dibangku sekolah. Sekolah yang dapat dijadikan mitra dalam upaya ini antara lain sekolah yang siswanya sebagian besar perempuan sehingga edukasi yang akan diberikan tepat sasaran. Berdasarkan survey, diketahui bahwa siswi di SMK Nahdlatul Ulama belum pernah mendapatkan edukasi tentang Peningkatan Pengetahuan tentang Kesehatan Reproduksi Remaja dengan Metode Teleconfrence Pelaksanaan kegiatan pengabdiaan kepada masyarakat ini dilakukan dengan metode pemberian edukasi pada siswa SMK Nahdlatul Ulama secara online menggunakan platform zoom meeting. Persentase hasil evaluasi sebelum diberikan edukasi masuk dalam kategori kurang paham sebanyak 13,88%, cukup paham 21,82%, pemahaman yang baik 56,71% dan sangat baik 7,59%. Pemahaman siswa perempuan mengalami peningkatan setelah diberikan edukasi yaitu termasuk dalam kategori sangat baik sebesar 28,82%, baik 53,94%, cukup 7,82% dan kurang sebanyak 9,42%. Dengan demikian diketahui bahwa setelah diberikan edukasi terdapat peningkatan pemahaman siswa tentang Kesehatan Reproduksi Remaja. Berdasarkan analisis statistik (uji Wilcoxon) didapatkan nilai signifikansi 0,002< 0,05 yang berarti terdapat perbedaan bermakna pada tingkat pengetahuan antara sebelum dan setelah edukasi.Peningkatan Pengetahuan tentang Kesehatan Reproduksi Remaja putri dengan Metode Teleconfrence.